2018
DOI: 10.1038/s41419-018-0910-5
|View full text |Cite
|
Sign up to set email alerts
|

PDI-mediated S-nitrosylation of DRP1 facilitates DRP1-S616 phosphorylation and mitochondrial fission in CA1 neurons

Abstract: Dynamin-related protein 1 (DRP1) is a key molecule to regulate mitochondrial fission. DRP1 activity is modulated by phosphorylation and S-nitrosylation on serine and cysteine residues, respectively. However, it is still unexplored whether S-nitrosylation of DRP1 affects its phosphorylation. In the present study, we found that Nω-nitro-l-arginine methyl ester hydrochloride (l-NAME, a NOS inhibitor) abolished S-nitrosylated (SNO-DRP1) and DRP1-serine (S) 616 phosphorylation levels in CA1 neurons under physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 74 publications
5
75
0
Order By: Relevance
“…Consistent with our previous studies ( Kim et al, 2017c ; Lee and Kim, 2018 ), PDI siRNA effectively reduced PDI expression, its activity and S -nitrosylation of dynamin-related protein 1 (DRP1, p < 0.05 vs. control siRNA; Supplementary Figures 1 , 12 ). These findings confirm the efficacy of PDI siRNA in the present study.…”
Section: Resultssupporting
confidence: 91%
“…Consistent with our previous studies ( Kim et al, 2017c ; Lee and Kim, 2018 ), PDI siRNA effectively reduced PDI expression, its activity and S -nitrosylation of dynamin-related protein 1 (DRP1, p < 0.05 vs. control siRNA; Supplementary Figures 1 , 12 ). These findings confirm the efficacy of PDI siRNA in the present study.…”
Section: Resultssupporting
confidence: 91%
“…However, Bossy et al, who believe this conclusion is controversial, have demonstrated that S ‐nitrosylation of Drp1 exerts no effect on the oligomerization of Drp1 and the progression of the AD. Hence, at present, it is obvious that S‐nitrosylation of Drp1 may not be uniquely responsible for NO‐induced mitochondrial fission (Haun et al, ; Lee & Kim, ; Lopez‐Sanchez, Lopez‐Pedrera, & Rodriguez‐Ariza, ; Nakamura & Lipton, ; Nakamura et al, ; Rizza et al, ).…”
Section: Posttranlational Modification Of Drp1 In Neural System Dysfumentioning
confidence: 99%
“…Dynamic post-translational modification of Drp1 alters its ability to promote mitochondrial fission and through its functions, the ER additionally contributes to the regulation of these modifications. Increased cytosolic calcium promotes activation of Drp1 by dephosphorylation at S637 [15,16], while the ER resident protein disulfide isomerase (PDI) has been shown to alter S-nitrosylation and phosphorylation of Drp1 to modify mitochondrial morphology in neurons [17].…”
Section: Introductionmentioning
confidence: 99%